The Effect of Liquid Organic Fertilizer Concentration on Kirinyuh Leaves on the Growth and Production of Cabbage Plants (Brassica Oleracea Var. Capitata) - Anti, Wa Ode; Roswuro, Roswuro; Hidayat, La Ode; Ramisa, Starni; Finalti, Finalti (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2024)
This research aims to determine the effect of the concentration of liquid organic fertilizer made from kirinyuh leaves on the growth and production of cabbage plants. The research was conducted in Bangkali Village, Watopute District, Muna Regency, Southeast Sulawesi Province, from June to September 2022. The materials used included K-K Cross hybrid cabbage seeds, kirinyuh leaves, EM4, brown sugar, water, and goat manure. The tools used were buckets, measuring tapes, gembors, hoes, tembilang, machetes, warings, analytical scales, boards, label paper, cell phone cameras, and writing tools. The research was structured based on a Randomized Block Design (RAK) with five treatments: without liquid organic fertilizer made from kirinyuh leaves (K0), liquid organic fertilizer made from kirinyuh leaves with a concentration of 80 ml L-1 of water (K1), liquid organic fertilizer made from kirinyuh leaves with a concentration of 90 ml L-1 of water (K2), liquid organic fertilizer made from kirinyuh leaves with a concentration of 100 ml L-1 of water (K3), and liquid organic fertilizer made from kirinyuh leaves with a concentration of 110 ml L-1 of water. The parameters observed were plant height (cm) at 3, 6, and 9 weeks after planting, number of leaves (strands) at 3, 6, and 9 weeks after planting, age of crop emergence (days), crop diameter (cm) at 9, 10, 11, and 12 weeks after planting, crop weight (grams), and production (tons/ha). The results of the research showed that the application of liquid organic fertilizer made from kirinyuh leaves had a very significant effect on plant height, number of leaves, age at which the crop emerged, crop diameter, crop weight, and cabbage production. The treatment with a concentration of 110 ml L-1 of water provided the best growth and production of cabbage, with an average of 30.72 tons/ha.